2009
DOI: 10.1007/s00425-009-0910-x
|View full text |Cite
|
Sign up to set email alerts
|

FORMOSA controls cell division and expansion during floral development in Antirrhinum majus

Abstract: Control of organ size is the product of coordinated cell division and expansion. In plants where one of these pathways is perturbed, organ size is often unaffected as compensation mechanisms are brought into play. The number of founder cells in organ primordia, dividing cells, and the period of cell proliferation determine cell number in lateral organs. We have identified the Antirrhinum FORMOSA (FO) gene as a specific regulator of floral size. Analysis of cell size and number in the fo mutant, which has incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 59 publications
0
45
0
Order By: Relevance
“…In recent studies, partial cDNA of a putative ANT-like ortholog with the AP2 domains in Antirrhinum majus was cloned using a yeast one-hybrid approach; the open reading frame (ORF) of ANT (Am-ANT) of A. majus was not been determined (Delgado-Benarroch et al, 2009). The reported sequence for Am-ANT is similar to the NtANTL and At-ANT genes.…”
Section: Research Reportmentioning
confidence: 96%
See 3 more Smart Citations
“…In recent studies, partial cDNA of a putative ANT-like ortholog with the AP2 domains in Antirrhinum majus was cloned using a yeast one-hybrid approach; the open reading frame (ORF) of ANT (Am-ANT) of A. majus was not been determined (Delgado-Benarroch et al, 2009). The reported sequence for Am-ANT is similar to the NtANTL and At-ANT genes.…”
Section: Research Reportmentioning
confidence: 96%
“…The reported sequence for Am-ANT is similar to the NtANTL and At-ANT genes. In situ hybridization in A. majus to analyze the expression of Am-ANT revealed that Am-ANT was expressed in floral meristems and in early floral organ primordia (Delgado-Benarroch et al, 2009). As floral organs matured, the expression of Am-ANT decreased in sepals at an early stage and in stamens at a late stage.…”
Section: Research Reportmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, a compensation mechanism that shows a decrease in cell size and increased cell division has been described for integument development in Arabidopsis (Truernit and Haseloff 2008), suggesting that tissues other than leaves might share this mechanism of growth control. Furthermore, we have found a similar phenotype in the formosa mutant of A. majus characterised by increased petal size and smaller cells (Delgado-Benarroch et al 2009). In the present work, we showed that the mutant coan affected petal, stamen and style development by cell division.…”
Section: A Compensation Mechanism In Petal Developmentmentioning
confidence: 71%